Enhanced marine monitoring and toxicity study of oil spill dispersants including Corexit EC9500A in the presence of diluted bitumen. Issue 7 (6th June 2020) - Brunswick, Pamela; MacInnis, Ceara Y.; Yan, Jeffrey; Buday, Craig; Fieldhouse, Ben; Brown, Carl E.; van Aggelen, Graham; Shang, Dayue
Abstract: Observations made for the analysis of the oil spill dispersant tracer dioctyl sulfosuccinate (DOSS) during LC50 toxicity testing, highlighted a stability issue for this tracer compound in seawater. A liquid chromatography high-resolution quadrupole time-of-flight mass spectrometry (LC/QToF) was used to confirm monooctyl sulfosuccinate (MOSS) as the only significant DOSS breakdown product, and not the related isomer, 4-(2-ethylhexyl) 2-sulfobutanedioate. Combined analysis of DOSS and MOSS was shown to be applicable to monitoring of spill dispersants Corexit® EC9500A, Finasol OSR52, Slickgone NS, and Slickgone EW. The unassisted conversion of DOSS to MOSS occurred in all four oil spill dispersants solubilized in seawater, although differences were noted in the rate of MOSS formation. A marine microcosm study of Corexit EC9500A, the formulation most rapid to form MOSS, provided further evidence of the stoichiometric conversion of DOSS to MOSS under conditions relevant to real world dilbit spill. Results supported combined DOSS and MOSS analysis for the monitoring of spill dispersant in a marine environment, with a significant extension of sample collection time by 10 days or longer in cooler conditions. Implications of the unassisted formation of MOSS and combined DOSS:MOSS analysis are discussed in relation to improving dispersant LC50 toxicity studies.